Approximation problems in analysis and probability - Heble, M. P. (North-Holland mathematics studies ;, 1989)
This is an exposition of some special results on analytic or C & infin;-approximation of functions in the strong sense, in finite- and infinite-dimensional spaces. It starts with H. Whitney's theorem on strong approximation by analytic functions in finite-dimensional spaces and ends with some recent results by the author on strong C & infin;-approximation of functions defined in a separable Hilbert space. The volume also contains some special results on approximation of stochastic processes. The results explained in the book have been obtained over a span of nearly five decades.